(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The normal course of biochemical and physiological processes that ensure the vital activity of the organism, among other systems, also depends on the normal functioning of the respiratory system. A number of external and internal factors can affect the indicators of respiratory movements: frequency, depth, respiratory volume: atmospheric pressure, the amount of oxygen in the atmosphere, the ecological state of the environment, various pathologies of the organism, etc., which become the cause of diseases. In the risk group of these diseases are the inhabitants of the areas near the ecologically unfavorable environment, especially the open mines, particularly the school children of that region. It is possible to reduce these risks and prevent diseases of the mentioned systems by the method of special breathing exercises. Residents of ecological regions, in particular adolescents, are at risk. This risk can be reduced by using the breathing exercise method. The purpose of this study was testing the effectiveness of these exercises on the indicators of the respiratory system of teenagers in the Vardenis Region.